A Review on Current Food Allergy - de Silva, Ganiesha; Marapana, RAUJ (Journal of Food Science and Technology Nepal, 2014)
Nowadays food allergy is recognized as an important food safety issue and it is widely debated world-wide. So, the food industry necessity takes the greatest care to assist those, who suffer allergies to select a suitable diet with confidence. Food allergy might be true food allergy or pseudo-allergy (food intolerance). The prevalence of food allergy is estimated much lower than are perceived by the public. That occurrence of food allergy has been estimated recently at 3-4% for adults and approximately 6-8% for young children and infants in the past decade. The most common food allergens are milk, egg, tree nut, soya, fish, some fruit (pineapple, citrus) and vegetables (tomato, mushroom) other than that food containing histamine, preservative, antioxidant, colouring, flavouring and whitening agents also cause food allergic reactions in some persons. Food allergy symptoms are unique to individual and common symptoms are nausea, abdominal pain, vomiting, diarrhea and itching. If someone misunderstanding about food allergy could result unnecessary food restriction. So, it is important to know the proper facts about this condition. The main aim of this review is to discuss the recent literature on overview discussion of current food allergy. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10562 J. Food Sci. Technol. Nepal, Vol. 7 (14-21), 2012